CALHM1 P86L polymorphism does not alter amyloid-β or tau in cerebrospinal fluid - Giedraitis, Vilmantas (2009)
Recently, the P86L alteration in CALHM1 (calcium homeostasis modulator-1) was reported to be associated with Alzheimer’s disease (AD). Moreover, the risk allele increased amyloid-β (Aβ) levels in conditioned media from cultured cells. Therefore, we hypothesized that CALHM1 P86L may modulate Aβ or tau levels in cerebrospinal fluid (CSF). Nearly 200 individuals with AD or other cognitive disorders were included for CSF analysis and CALHM1 genotyping. No significant differences in CSF levels of Aβ42, tau or phospho-tau were found across the various CALHM1 genotypes. In conclusion, we found no evidence that CALHM1 P86L is associated with altered CSF levels of the investigated AD biomarkers.